1996
DOI: 10.1111/j.1151-2916.1996.tb07998.x
|View full text |Cite
|
Sign up to set email alerts
|

Grain Boundary Mobility in Y2O3: Defect Mechanism and Dopant Effects

Abstract: The effects of the dopants, Mg2+, Sr2+, Sc3+, Yb3+, Gd3+, La3+, Ti4+, Zr4+, Ce4+, and Nb5+, on the grain boundary mobility of dense Y2O3 have been investigated from 1500° to 1650°C. Parabolic grain growth has been observed in all cases over a grain size from 0.31 to 12.5 μm. Together with atmospheric effects, the results suggest that interstitial transport is the rate‐limiting step for diffusive processes in Y2O3, which is also the case in CeO2. The effect of solute drag cannot be ascertained but the anomalous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
170
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(180 citation statements)
references
References 27 publications
7
170
0
3
Order By: Relevance
“…The Y 3+ interstitial concentration and the O 2− vacancy concentration demonstrate a positive relationship between each other in Y 2 O 3 which is presented in formula (1). 23 Therefore, the doping of Zr 4+ led to a lower concentration of Y 3+ interstitial, and hence a lower mobility of grain boundary in Y 2 O 3 ceramic.…”
Section: Densification and Microstructurementioning
confidence: 98%
See 3 more Smart Citations
“…The Y 3+ interstitial concentration and the O 2− vacancy concentration demonstrate a positive relationship between each other in Y 2 O 3 which is presented in formula (1). 23 Therefore, the doping of Zr 4+ led to a lower concentration of Y 3+ interstitial, and hence a lower mobility of grain boundary in Y 2 O 3 ceramic.…”
Section: Densification and Microstructurementioning
confidence: 98%
“…This indicated that the La 3+ ions enhanced the mobility of grain boundary while the Zr 4+ ions strongly suppressed the migration of grain boundary, coinciding with the published literatures. 14,17,19,[20][21][22][23] Considering the Y 2 O 3 structure with one fourth of anion sites vacant, 24 the O 2− ions diffuse much faster than Y 3+ ions. Moreover, as profoundly investigated, 23,25 the diffusion of Y 3+ interstitial is ascertained to be the controlling step of sintering process in Y 2 O 3 ceramic rather than Y 3+ vacancy.…”
Section: Densification and Microstructurementioning
confidence: 99%
See 2 more Smart Citations
“…The average grain size was determined to be 22 µm by multiplying the average interpreting grain size with a correlation factor of 1.56 [11] . The mass transfer mechanism in the sintering process of Y 2 O 3 ceramic has been investigated by Chen et al [12] . The diffusion of Y 3+ interstitials is considered as the controlling step of the grain boundary migration.…”
mentioning
confidence: 99%